2003
DOI: 10.1002/bit.10585
|View full text |Cite
|
Sign up to set email alerts
|

Laser impact assessment in a biofilm‐forming bacterium Pseudoalteromonas carrageenovora using a flow cytometric system

Abstract: Impact by pulsed laser irradiations from an Nd:YAG laser on the marine biofilm-forming bacterium Pseudoalteromonas carrageenovora has been studied using a flow cytometric system. The biofilm-forming bacteria in the planktonic state have been irradiated while flowing, and the mortality and bacterial attachment have been determined by exposing TiN coupons in the system. Coupons suspended in the non-irradiated bacterial flow were treated as the control. The fluence used in the study was 0.1 J/cm(2). Three flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Investigations on bacteria, micro algae, and the larvae of biofouling organisms showed that low power pulsed radiation significantly damaged these organisms. The organisms exposed to laser irradiation showed a significantly lower rate of settlement compared to the non-irradiated control (Nandakumar et al, 2003a and2003b). The studies have also demonstrated that, irradiation of the water column containing bacteria resulted in 'a significantly reduced rate of biofilm formation as compared to the control.…”
Section: Antifouling Coatingsmentioning
confidence: 84%
“…Investigations on bacteria, micro algae, and the larvae of biofouling organisms showed that low power pulsed radiation significantly damaged these organisms. The organisms exposed to laser irradiation showed a significantly lower rate of settlement compared to the non-irradiated control (Nandakumar et al, 2003a and2003b). The studies have also demonstrated that, irradiation of the water column containing bacteria resulted in 'a significantly reduced rate of biofilm formation as compared to the control.…”
Section: Antifouling Coatingsmentioning
confidence: 84%